Mentefacto conceptual para la función de onda de la mecánica cuántica - Guevara M., Elisa; Everth T., Maureen; Organista R., Orlando (Revista Científica, 2011)
Quantum mechanics represents a challenge for current research in physics education, largely because the phenomena that occur on a microscopic scale have reduce deep-rooted intuitions, for example the idea of the path of a body (trajectory), the idea of locating an object in a place (place), or the idea of determining exactly the result of ameasurement (determinism). The researcher Lei Bao focused his study on several topics that he considers essential to have a good understanding of quantum mechanics; one of these topics is the probabilistic interpretation of the wave function. In this article we conduct a conceptual analysis of the wave function through a cognitive diagram called cognitive mind-fact; this ideogram helps identify and organize constituent and differentiating concepts implicit in the concept of wave function and represent a contribution to the teaching-learning concept.